PELAKSANAAN SYARI’AT ISLAM DI ACEH SEBAGAI BAGIAN WILAYAH NEGARA KESATUAN REPUBLIK INDONESIA (NKRI) - Syamsul Bahri (Jurnal Dinamika Hukum, 2012)
The application of Sharia law is not a new thing in Indonesia, especially in Aceh. Since pre independent day of Indonesia, Aceh had been famous with its Islamic Empires, such as Samudra Pasai and Aceh Darussalam empires. Nowadays, such law is still applied by the people. However, in applying such law there are some constraints as a result of there is no fix and clear form that can be guidance in Aceh. The efforts done to find the suitable formula for such application are still conducted in every life activity that in the future might give its own characteristic in legal and political studies in Indonesia.  Key words : Sharia Law, special authonomy and Qanun